Editorial - Aguirre Chávez, Felipe (2021)
With the beginning of the XXI century there have been rapid and profound changes in society and this has led to the proposition of new educational theories and practices. In the words of Marino Latorre, director of the Marcelino Champagnat University Graduate School, “when the context changes, everything changes; society changes, relationships between people, human needs, etc. change. and all this involves education. If we educate children and young people today as we educated them yesterday, are we not educating them for a world that no longer exists? Aren't we stealing their future from them? " .